OC-100 The clonal origins of gastric adenocarcinoma. (28th May 2012) - Garcia, T Ventayol; Rodriguez-Justo, M; Graham, T; Novelli, M; Wright, N; McDonald, S
Abstract : Introduction: We have previously shown that entire fields of dysplasia in the human stomach are derived from a single mutated, metaplastic gland. 1 This suggests that intestinal metaplasia (IM) can be considered a field defect among which dysplasia can arise and this would indicate that adenocarcinomas derived from such dysplasia would also be clonal. Recent work published by our laboratory has indicated that familial adenomatous polyposis–associated colorectal adenomas as well as some sporadic lesions 2 and dysplasia within Barrett's oesophagus 3 are polyclonal. There is therefore a need to ascertain the clonality of gastric adenocarcinomas (GA). Methods: Here we screened a large cohort of GA patients for mutations in genes accounting for nearly 90% of reported mutations in GA in order assess mutation frequencies. The screening was then followed by laser capture microdissection PCR sequencing and loss of heterozygosity (LOH) analysis of the mutated specimens in order to assess clonality of GA from dysplasia and IM. Results: From the 51 patients cohort we have found 18 patients (35.3%) presenting mutations, but only one out of the 51 patients (1.9%) presented two independent mutations in a single cancer. We found 3 mutations in APC (6.3%), one in CDKN2A (2.2%), 13 in TP53 (27.7%), one in CTNNB1 (2.2%) and one in K-RAS (2.4%), but none in PIK3CA or PTEN. Our mutation frequencies are comparable to previous reports, however we observed that most functional mutations occurred as a single event despite screening multiple genes. Analysis of the multiple laser capture microdissected areas revealed multiple genotypes within the same cancer in three out of the five patients. Moreover, current LOH data shows LOH of chromosome 17 in IM and throughout the cancers in all different genotypes, suggesting that chromosome 17 LOH might have been the first hit mutation followed by mutations in TP53, and in one patient a subsequent CTNNB1 mutation. Conclusion: This suggests that cancer progression may have been initiated by LOH in intestinal metaplasia and that GA cells might become genetically diverse as the cells evolve in the tumour. Therefore, IM is likely to represent a field defect for gastric cancer. Competing interests: None declared. References: 1. Gutierrez-Gonzalez L, Graham TA, Rodriguez-Justo M, et al. The clonal origins of dysplasia from intestinal metaplasia in the human stomach. Gastroenterology 2011;140 :1251–60. 2. Thirlwell C, et al. Clonality assessment and clonal ordering of individual neoplastic crypts shows polyclonality of colorectal adenomas. Gastroenterology 2010;138 :1441–54. 3. Leedham SJ, et al. Individual crypt genetic heterogeneity and the origin of metaplastic glandular epithelium in human Barrett's oesophagus. Gut 2008;57 :1041–8.